2020
DOI: 10.1007/s10796-020-10040-5
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Based LSTM Network for Rumor Veracity Estimation of Tweets

Abstract: Twitter has become a fertile place for rumors, as information can spread to a large number of people immediately. Rumors can mislead public opinion, weaken social order, decrease the legitimacy of government, and lead to a significant threat to social stability. Therefore, timely detection and debunking rumor are urgently needed. In this work, we proposed an Attention-based Long-Short Term Memory (LSTM) network that uses tweet text with thirteen different linguistic and user features to distinguish rumor and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The proliferation of social media has been a catalyst to inducing a dangerous, socio-cultural polarisation of society (Montalvo & Reynal-Querol, 2005 ; Spohr, 2017 ; Vishwanath, 2015 ). This polarisation phenomenon has led researchers to explore SMIP from different theoretical lenses to study specific social media platforms and particular attention given to fake news (Langley et al, 2021 ; Brummette et al, 2018 ; Lee et al, 2015a ; Shearer & Grieco, 2019 ; Singh et al, 2020 ). Manifestations of SMIP include misinformation about presidential election campaigns (Guess et al, 2018 ; Linvill & Warren, 2020 ; Schäfer et al, 2017 ), race (Jamieson, 2020 ), immigration (Jaramillo-Dent & Pérez-Rodríguez, 2021 ; Newman et al, 2017 ), religion (Said, 2008 ), and pandemics, specifically Covid-19 (Laato et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proliferation of social media has been a catalyst to inducing a dangerous, socio-cultural polarisation of society (Montalvo & Reynal-Querol, 2005 ; Spohr, 2017 ; Vishwanath, 2015 ). This polarisation phenomenon has led researchers to explore SMIP from different theoretical lenses to study specific social media platforms and particular attention given to fake news (Langley et al, 2021 ; Brummette et al, 2018 ; Lee et al, 2015a ; Shearer & Grieco, 2019 ; Singh et al, 2020 ). Manifestations of SMIP include misinformation about presidential election campaigns (Guess et al, 2018 ; Linvill & Warren, 2020 ; Schäfer et al, 2017 ), race (Jamieson, 2020 ), immigration (Jaramillo-Dent & Pérez-Rodríguez, 2021 ; Newman et al, 2017 ), religion (Said, 2008 ), and pandemics, specifically Covid-19 (Laato et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In machine learning, a massive number of studies have proposed different models of machine learning algorithms like naïve Bayes (NB), support vector machine (SVM), logistic regression (LR), and many other models [2], [8]- [11], Our focus is on naïve Bayes model, many fake news detections have been implemented using NB as in the second model of the work done by [12], NB achieved 56% accuracy among 7 other classifiers using linguistic and user features. The work [13] shows the model NB classified the second in accuracy after SVM with 55.85%, authors in [14] achieved the highest accuracy of 80% using bayesian classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Asghar et al [20] suggested a rumor classification model proposed by merging bi-long-short term memory (BiLSTM) with CNN. Moreover, Singh et al [12] proposed an attention-based LSTM network that distinguishes rumor and non-rumor tweets using tweet text and 30 different linguistic and user features. The performance of the model reached 88% against the other conventional machine and deep learning models.…”
Section: Related Workmentioning
confidence: 99%
“…Singh et al. ( 2020 ) used attention-based LSTM to classify rumor and non-rumor tweets with thirteen linguistic and user profile features and achieved an F1-score of 88%. Horne and Adali ( 2017 ) developed support vector machine (SVM) model for fake news detection using three linguistics features categories: writing pattern, text complexity, and psychological.…”
Section: Related Workmentioning
confidence: 99%